PLACE OF PHOTODYNAMIC THERAPY IN THE TREATMENT OF CARIES IN INDIVIDUALS WITH GENETIC DETERMINATION TO CARIOUS DISEASE - A.M. Pariy; N.A. Zelinskaya; O.A. Znachkova; M.Yu. Antonenko (Bogomolets National Medical University, 2016)
Prevention of carious disease and its complications continue to take a leading position among dental health problems in Eastern Europe. The feasibility of antiseptic treatment of carious cavities is controversial depending on the nature of the caries process flow, in people with different levels of genetic determination to carious disease in particular. Research was done on the necessity of the introduction of photodynamic therapy in the treatment regimen of acute and chronic deep caries in caries- determined people. The research is based on the observation of 162 patients aged 18-25 years with caries, with a high level of genetic determinism to carious disease at A (II) B (III) Rh-, divided in to clinical groups depending on the course of deep caries and the use of photodynamic therapy for antiseptic treatment. 0.1% aqueous solution of toluidine blue was used as a photo sensitizer which was irradiated low-energy laser radiation of dental diode laser Elexxion Claros Pico (Germany) with a wavelength of 635 nm, power output of 100 mV, and 1.8 J of energy dose. The analysis of the immediate and long-term results of treatment proved that the use of photodynamic therapy facilitates the effectiveness of treatment and improves the treatment prognosis of acute deep caries in people with their genetic determination. However, the feasibility of including this method in the treatment algorithm for chronic deep caries course wasn't proven.